Genetic basis of resistance to leaf rust in tetraploid wheats - Desiderio F.; Guerra D.; Mastrangelo A.M.; Rubiales D.; Pasquini M.; Simeone R.; Blanco A.; Cattivelli L.; Valè G. (Proceedings of the International Symposium on Genetics and breeding of durum wheat, 2014)
Leaf rust, caused by Puccinia triticina Eriks., is one of the major constraints to durum wheat production. It is globally distributed with different race structures that continuously evolve and form novel virulent races. Growing resistant cultivars represent the most effective way of controlling rust diseases in wheat. In this paper we report a summary about the leaf rust genes (Lr), the quantitative trait loci (QTLs) and significant regions detected in tetraploid wheats.
International Symposium : Genetics and Breeding of Durum Wheat, 2013/05/27-30, Rome (Italy)